Cognitive function, mood, and sleep quality in patients treated with intensity‐modulated radiation therapy for nasopharyngeal cancer: a prospective study. Issue 10 (11th April 2014) - Mo, Yan‐Lin; Li, Ling; Qin, Ling; Zhu, Xiao‐Dong; Qu, Song; Liang, Xia; Wei, Zhou‐Ji
Abstract Objective The aim of this study was to prospectively evaluate the cognitive function, depression, anxiety, and sleep quality in patients with nasopharyngeal cancer (NPC) before and after intensity‐modulated radiotherapy (IMRT). Methods Eligible patients with newly diagnosed NPC treated with primary IMRT were recruited. A series of neuropsychological tests were performed within 1 week before and after IMRT. Cognitive function was measured with the Das–Naglieri cognitive assessment system. The Self‐rating Anxiety Scale and Self‐rating Depression Scale were used to assess mood states. Sleep quality was evaluated by means of the Pittsburgh Sleep Quality Index. Results A total of 51 patients were enrolled. The overall prevalence of depression, anxiety, and poor sleep quality showed a significant increase after RT, compared with their pre‐RT levels (39.2% vs. 3.9%, p = 0.000; 19.6% vs. 3.9%, p = 0.039; 64.7% vs. 37.3%, p = 0.003, respectively). Multiple linear regression analysis revealed that pre‐RT depression and younger age and pre‐RT anxiety and younger age were significant predictors of post‐RT depression and anxiety, respectively (p < 0.05). Poor sleep quality before treatment was also associated with poor sleep after RT (p = 0.032). However, the cognitive function evaluated by the cognitive assessment system from pre‐RT was similar to the post‐RT results. Conclusions Exposure to ionizing radiation for the treatment of NPC decreased mood and sleep quality following IMRT, especially for patients with depression, anxiety, younger age, or poor sleep before treatment. No acute cognitive deficits were found resulting from IMRT, but the long‐term effects of RT might still warrant concern. Copyright © 2014 John Wiley & Sons, Ltd.